Modeling Evaporation of Water Droplets as Applied to Survival of Airborne Viruses - Leonid A. Dombrovsky; Alexander A. Fedorets; Vladimir Yu. Levashov; Alexei P. Kryukov; Edward Bormashenko; Michael Nosonovsky (Atmosphere, 2020)
Many viruses, such as coronaviruses, tend to spread airborne inside water microdroplets. Evaporation of the microdroplets may result in a reduction of their contagiousness. However, the evaporation of small droplets is a complex process involving mass and heat transfer, diffusion, convection and solar radiation absorption. Virological studies indicate that airborne virus survival is very sensitive to air humidity and temperature. We employ a model of droplet evaporation with the account for the Knudsen layer. This model suggests that evaporation is sensitive to both temperature and the relative humidity (RH) of the ambient air. We also discuss various mechanisms such as the effect of solar irradiation, the dynamic relaxation of moving droplets in ambient air and the gravitational sedimentation of the droplets. The maximum estimate for the spectral radiative flux in the case of cloudless sky showed that the radiation contribution to evaporation of single water droplets is insignificant. We conclude that at small and even at moderately high levels of RH, microdroplets evaporate within dozens of seconds with the convective heat flux from the air being the dominant mechanism in every case. The numerical results obtained in the paper are in good qualitative agreement with both the published laboratory experiments and seasonal nature of many viral infections. Sophisticated experimental techniques may be needed for in situ observation of interaction of viruses with organic particles and living cells within microdroplets. The novel controlled droplet cluster technology is suggested as a promising candidate for such experimental methodology.